Control strategy of a dual induction motor: Anti-slip control application. (March 2015) - Achour, Tahar; Debbou, Mustapha; Pietrzak-David, Maria
Abstract: The paper deals with a Dual Induction Motor control. A control strategy based on the Average Differential Control (ADC) is developed and adapted to work as an anti-slip control in a railway traction system. In addition to cancel the behaviour deviation between the motors supplied by a single inverter in case of an adhesion loss (or an unbalanced load), the proposed control strategy permits an action on the torque control to cancel the differential torque between the two motors. The control strategy is validated on a laboratory test bench with a Mechanical Railway Traction Load Emulator. Abstract : Highlights: A Cooperative Control strategy of a Dual Induction Motor control is developed. The control strategy is used as an anti-slip control in a railway traction system. A Sensitivity Analysis of the drive control is performed. The control strategy is validated on a laboratory test bench.